156. Clinical Characteristics and Acute-phase Cytokine Response of Solid-Organ Transplant Recipients with Bloodstream Infections Differs According to Bacterial Type and Transplant Status - Eichenberger, Emily; Ruffin, Felicia; Jung, Sin-Ho; Lerebours, Reginald; Sharma-Kuinkel, Batu K; Alexander, Barbara D; Thaden, Joshua; Fowler, Vance G; Maskarinec, Stacey (Open forum infectious diseases, 2019)
Background Clinical outcomes and host immune response in solid-organ transplant recipients (Tx) with Staphylococcus aureus bacteremia (SAB) and Gram-negative bacteremia (GNB) are poorly understood. The aims of this study were to describe (1) clinical characteristics and outcomes and (2) acute-phase cytokine response in Tx recipients with SAB and GNB as compared with matched non-transplant subjects (Non-Tx). Methods Thirty-two Tx recipients who were prospectively enrolled in the Blood Stream Infection Biorepository (BSIB) were matched 1:1 with Non-Tx patients on age, race, gender and bacteria using a perfect matching algorithm (Tx-SAB n = 16, Non-Tx SAB n = 16; Tx GNB n = 16, Non-Tx GNB n = 16). GNB included Escherichia coli (n = 16) and Klebsiella pneumoniae (n = 16). Multiplex cytokine testing was performed (Luminex) to evaluate acute-phase serum cytokines levels. Baseline characteristics were summarized using mean with standard deviation (SD), median with interquartile range (IQR), and ranges (min and max), or frequency with %. Differences between the Tx and Non-Tx SAB and GNB were compared using either the equal or unequal variance version of the Student’s t-test or Wilcoxon rank-sum test for continuous variables. Fisher’s exact test was used for categorical variables. Results An endovascular source was more common in Tx SAB vs. Non-Tx SAB (75.0% vs. 0.0%; P = 0.0003) and Tx-GNB (42.9% vs. 18.8%; P = 0.006). Fewer SAB cases were attributed to a skin/soft tissue/osteoarticular in Tx vs. Non-Tx (8.3% vs. 91.7%; P = 0.0001). APACHE II scores were higher in Tx SAB vs. Non-Tx SAB (14.0 [IQR: 11.0, 17.5] vs. 10.0 [IQR: 7.0, 12.5] P = 0.02), but not between Tx GNB vs. Non-Tx GNB (14 [IQR: 12.0, 15.5] vs. 13.5 [12.0, 15.0] P = 0.54). No significant difference length of stay, recurrent bacteremia or mortality were noted among or between groups. Patients with SAB had significantly higher levels of IL-10, CCL5, eotaxin vs. GNB in both Tx and Non-Tx. Conversely, IL-5, IL-13 and IL-17 levels were significantly lower in SAB compared with GNB in both Tx and Non-Tx. Within Tx alone, IL-8 and IL-15 were significantly higher in SAB as compared with GNB. Conclusion Significant differences exist in etiology and host immune response in Tx and Non-Tx with SAB and GNB. Further research is needed to understand the host immune response to BSI in these patients. Disclosures All authors: No reported disclosures.